2017
DOI: 10.1105/tpc.17.00440
|View full text |Cite
|
Sign up to set email alerts
|

DISTAG/TBCCd1 Is Required for Basal Cell Fate Determination in Ectocarpus

Abstract: Brown algae are one of the most developmentally complex groups within the eukaryotes. As in many land plants and animals, their main body axis is established early in development, when the initial cell gives rise to two daughter cells that have apical and basal identities, equivalent to shoot and root identities in land plants, respectively. We show here that mutations in the Ectocarpus DISTAG (DIS) gene lead to loss of basal structures during both the gametophyte and the sporophyte generations. Several abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 86 publications
1
55
0
Order By: Relevance
“…2; [10,15]). Both generations consist of uniseriate, branched filaments, but there are some morphological differences between the two generations [15,16]. Gametophyte germlings are made up of a rhizoid and an upright filament, the latter consisting of cylindrical cells (Fig.…”
Section: Life Cyclementioning
confidence: 99%
See 3 more Smart Citations
“…2; [10,15]). Both generations consist of uniseriate, branched filaments, but there are some morphological differences between the two generations [15,16]. Gametophyte germlings are made up of a rhizoid and an upright filament, the latter consisting of cylindrical cells (Fig.…”
Section: Life Cyclementioning
confidence: 99%
“…Male and female gametes are released into the surrounding seawater, where they fuse to produce zygotes that initiate the sporophyte generation. Gametophytes and sporophytes are subtly different in terms of cell types, cell size and angle of branching [16]. The Ectocarpus life cycle also includes several alternative pathways (dashed arrows).…”
Section: Life Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…The basal cell forms filamentous rhizoids that anchor the algae to the substratum, analogous to roots in land plants. Godfroy et al (2017) identified an Ectocarpus mutant that does not produce rhizoids (see figure) and named this mutant distag (dis), which means "detached" in Breton. Ectocarpus has alternating gametophytic and sporophytic generations, which start from a single cell and develop similar structures.…”
mentioning
confidence: 99%